FORECASTING THE FINANCIAL CONDITION OF THE ENTERPRIZE ON THE BASIS OF INTEGRATION OF Z-MODELS - Kvasniy , Mariya; Tsyhanchuk , Roman (Socio-economic relations in the digital society, 2021)
This paper proposes to improve the method of predicting the probability of bankruptcy of the enterprise by using the system Z-models of Altman, Lis, Taffler and Tishaw and their integrated indicator. Based on the developed scientific and methodological approach, a concept has been developed to assess and predict possible negative changes in the financial condition and to diagnose the probability of bankruptcy for the enterprise PJSC «Lviv Locomotive Repair Plant». As a result of the study, it was found that the probability of bankruptcy of PJSC «Lviv Locomotive Repair Plant» during 2015—2018 varies from moderate to high. In 2017, the probability of bankruptcy reaches its maximum value, and in 2018 the financial condition of the company improves slightly, which reduces the risk of bankruptcy. The unstable state of the country’s economy, which has been observed in recent years, has had a negative impact on the company’s operations. The company has an unsatisfactory financial condition and unstable economic effect from its activities. Thus, the problem of loss and bankruptcy remains relevant and needs to be studied in more detail. The paper further develops scientific and methodological approaches to crisis management of the enterprise based on the development of methods for predicting possible expectations of negative changes in financial condition, in particular, determining the probability of bankruptcy of the enterprise by integrating Z-models. It is proved that the problem of losses and bankruptcy remains extremely relevant in time of deep economic volatility. Under such conditions, the issue of determining the probability of bankruptcy is particularly acute, because reliable and timely identification of negative factors affecting the financial and economic activities of the enterprise allows to form appropriate financial policies and develop measures to improve the efficiency of financial resources, increase solvency, ensure enterprise competitiveness. in the long run, and most importantly, to prevent the risk of bankruptcy. Prospects for further research in this area are issues related to improving the mechanism for predicting the probability of bankruptcy in terms of its components, existing criteria, the choice of a system of indicators, etc.
Keywords: enterprise crisis; financial condition; Z-models; integrated indicator; forecasting